2015
DOI: 10.1149/2.0201503jss
|View full text |Cite
|
Sign up to set email alerts
|

A Well-Controlled PSG Layer on Silicon Solar Cells against Potential Induced Degradation

Abstract: This study proposes a promising silicon (Si) solar cell structure for reducing the potential induced degradation (PID) of crystalline Si solar cells. Phosphorous silicate glass (PSG) layers were carefully designed on an emitter layer, and the thickness of these layers (d PSG ) was controlled by adjusting the diffusion temperature and time. The results show that the power loss remarkably decreased from 31% (d PSG = 0 nm) to 11% (d PSG = 22.3 nm) and further decreased to less than 5% after a 48-h PID test when d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…[30,35] However, such SiO 2 mitigates degradation for shunting-type PID. [37][38][39] This difference implies that the mechanisms of polarization-type PID and shunting-type PID are fundamentally different from one another.…”
Section: Sinxmentioning
confidence: 99%
“…[30,35] However, such SiO 2 mitigates degradation for shunting-type PID. [37][38][39] This difference implies that the mechanisms of polarization-type PID and shunting-type PID are fundamentally different from one another.…”
Section: Sinxmentioning
confidence: 99%
“…With this module, only the light-receiving side of the solar cell, i.e. the anti-reflection coating, which is more important for generating the PID phenomena, 3,12,[22][23][24][25][26][27][28][29][30] is encapsulated during the PV module fabrication. The single-encapsulation module can be analyzed directly after PID testing because the nonlight-receiving side of the module is in the air and because no pre-processing is required for micro-analyses of the PID phenomena of the whole cell.…”
Section: Introductionmentioning
confidence: 99%
“…Hara et al 24) have reported that TiO 2 thin films deposited on the inner surfaces of a cover glass can prevent PID for c-Si modules. Du et al 25) have shown that the PID of c-Si solar cells can be effectively reduced without influencing their efficiency by inserting phosphorus silicate glass (PSG) layers between the front n + emitters and the SiN x ARC layers. PID-affected modules can recover from the degradation by applying a positive bias.…”
Section: Introductionmentioning
confidence: 99%